Kandungan Zinc, Fe, Lemak dan Sifat Organoleptik Bakso Ikan Tongkol (Euthynnus affinis) dengan Jantung Pisang Kepok (Musa acuminata) sebagai Pangan Fungsional Pencegah Stunting: Zinc, Iron, Fat Content, and Organoleptic Properties of Tongkol Fish Meatballs (Euthynnus affinis) with Kepok Banana Blossom (Musa acuminata) as Functional Food for Preventing Stunting - Dewi Pertiwi Dyah Kusudaryati; Rahma Adiningrum; Agung Setya Wardana; Dodik Luthfianto (Universitas Airlangga, 2025)
Background: Stunting is commonly associated with deficiencies in micronutrients such as zinc and iron, as well as low fat intake in children. The use of nutrient-rich Tongkol fish and Kepok banana blossom for producing meatballs has the potential to prevent stunting. Objectives: This study aims to determine the zinc, iron, fat content, and the organoleptic properties of Tongkol fish meatballs added with Kepok banana blossom. Methods: The study employed a completely randomized design with three treatments, consisting of different ratios of Tongkol fish to Kepok banana blossom in groups F1 (60%:40%), F2 (50%:50%), and F3 (40%:60%). The zinc and iron content were analyzed using Atomic Absorption Spectroscopy (AAS), fat content was determined using the Soxhlet method, and organoleptic properties were assessed through hedonic testing. Data were analyzed using One-Way ANOVA and the Kruskal-Wallis test. Results: The highest zinc and iron content was observed in group F2, with values of 243.42±4.89 ppm and 405.40±16.45 ppm, respectively, while the highest fat content was found in groups F1 and F3, both at 0.52%. Statistical analysis revealed significant differences in zinc content (p-value<0.001) and iron content (p-value=0.001), while no significant difference was found in fat content (p-value=0.283). There was a significant difference in taste (p-value=0.028), but no significant differences were observed in color (p-value=0.182), aroma (p-value=0.853), and texture (p-value=0.820). Conclusions: The treatment group F2 exhibited the highest levels of zinc and iron, while the fat content did not show statistically significant differences. There was a difference in taste; however, no significant differences were observed in color, aroma, and texture in the organoleptic tests.